Disposition and metabolism of cabotegravir: a comparison of biotransformation and excretion between different species and routes of administration in humans. (1st February 2016) - Bowers, Gary David; Culp, Amanda; Reese, Melinda J.; Tabolt, Glenn; Moss, Lee; Piscitelli, Stephen; Huynh, Phuong; Wagner, David; Ford, Susan L.; Gould, Elizabeth P.; Pan, Rennan; Lou, Yu; et al.
Abstract: 1. Cabotegravir [( 3S, 11aR )- N -[(2, 4-difluorophenyl)methyl]-6-hydroxy-3-methyl-5, 7-dioxo-2, 3, 5, 7, 11, 11a-hexahydro[1, 3]oxazolo[3, 2-a]pyrido[1, 2-d]pyrazine-8-carboxamide] is an HIV-1 integrase inhibitor under development as a tablet for both oral lead-in therapy and long-acting (LA) injectable for intramuscular dosing. 2. Metabolism, pharmacokinetics and excretion were investigated in healthy human subjects who received either a single oral dose (28.2 mg) of [ 14 C]cabotegravir in a mass balance study, or LA formulations of unlabeled cabotegravir (200–800 mg), intramuscularly or subcutaneously, in a separate study. Metabolism, distribution and excretion of [ 14 C]cabotegravir were also investigated in mice, rats and monkeys. 3. Recovery of radioactivity in humans represented a mean total of 85.3% of the dose, including 26.8% in the urine. The mean apparent terminal phase half-life was similar for both cabotegravir and radioactivity, 39 h compared to 41 h. 4. Following oral, intramuscular and subcutaneous administration, cabotegravir was the major component in plasma and the glucuronic acid conjugate (M1) represented the predominant component in urine. Cabotegravir was present in bile along with its major metabolite (M1). 5. The primary metabolite of [ 14 C]cabotegravir in mouse, rat and monkey was the same as that in human. In vitro phenotyping experiments demonstrated that cabotegravir was metabolized by UDP-glucuronosyltransferase (UGT) 1A1 and UGT1A9.